Türkiye'de yeraltı gaz depolaması gereksinimi ve kuzey Marmara gaz sahasının depo olarak modellenmesi - Karaalioğlu, Hülya (Fen Bilimleri Enstitüsü, 1997)
Ülkemizde doğal gaz talebi gün geçtikçe artmaktadır. Ancak yeraltı depolaması olanakları henüz geliştirilmemiş olduğundan dolayı, yerleşim atanlarına doğal gaz verilmesi ve gaz miktarının arttırılmasının uygun olmadığı BOTAŞ yetkililerince belirtilmektedir. Bu ise Türkiye'de konutların doğal gaz tüketiminin planlanmasında depolamanın önemini açık olarak vurgulamakta, yeraltı deposu olanakları geliştirilmedikçe kentlerimizde konutlara verilecek doğal gaz miktarının arttırılması giderek zorlaşmaktadır. Doğal gaz,arzı ile talep arasındaki dengenin kurulması istenirse, dengenin kurulmasındaki en önemli sorunlar konutların yılın soğuk döneminde gazı talep etmesi ve sıcak dönemde ise talebin ihmal edilecek düzeyde olmasından kaynaklanmaktadır. Konutların ısıtılmasında tüketilen ve yıl içinde değişmeler gösteren gaz dağıtımında dengenin kurulabilmesi için soğuk dönemde arz edilen gazın bir bölümünün sıcak dönemde kullanılmayan ve dolayısıyla depolanan gazdan karşılanması en akılcı ve çağdaş çözümdür. Bu çalışmada, Türkiye'de doğal gaz boru hattının geçtiği veya geçmesinin planlandığı bölgelerdeki yerleşim alanlarındaki konutların doğal gaz tüketim potansiyeli tahmin edilerek, Kuzey Marmara gaz sahasının depo olarak kullanılması durumu incelenmiştir. Isıtma amacıyla gaz kullanan konutların doğal gaz tüketim potansiyelini belirleyebilmek amacıyla varolan, yapılmakta olan ve planlanan doğal gaz boru hatlarının geçtiği yerleşim alanlarındaki konutların % 100, 50 ve 25'inin ısıtma amaçlı gaz kullanması durumunda 1996, 2000, 2005 ve 2010 yıllarında olabilecek doğal gaz tüketim potansiyelleri belirlenmiştir. Boru hatlarının geçtiği yerleşim alanlarındaki konutların hepsinin (% 100) gaz kullanması durumunda doğal gaz tüketiminin 2010 yılında 16.4x109 sm3 olacağı tahmin edilmiştir. Oysa 2010 yılında doğal gaz arzının yaklaşık 30-50x109 sm3 arasında olacağı ve konut sektörü doğal gaz arzının yaklaşık 4.5-7.5 x109 sm3 olacağı tahmin edilmektedir. Bu ise konutların en çok % 46'sına gaz verilebileceği şeklinde yorumlanabilir. Gaz kullanımının yaygınlaştırılmasına paralel olarak kışın artan gaz talebinin depolardan karşılanabilmesi için ülkemizde henüz önemli somut adımlar atılmamıştır. Türkiye'deki depolama olanakları araştırıldığında bir seçenek olarak Kuzey Marmara gaz sahası incelenebilir. Bu sahanın depo olarak kullanılması durumunda var olan ve T.P.A.O. tarafından açılmış üç kuyuya ek kuyuların açılması gereklidir. Bugünlerde BOTAŞ tarafından iki yeni üretim kuyusu daha devreye sokulmaktadır. Ancak, toplam beş üretim kuyusunun bile bu sahanın bir yeraltı deposu olarak işletilmesi için yetersiz olacağı çalışmada gösterilmektedir, örneğin, işletilen gaz kapasitesinin 1.3x109 sm3 olması durumunda bu kapasitenin 100 günde üretilmesi veya enjekte edilebilmesi için yaklaşık 33 kuyu gereklidir. Bu sonuçlar, Türkiye'de konutların doğal gaz tüketiminin planlanmasında depolamanın önemini açıkça göstermekte ve en yakın zamanda depolama olanaklarının geliştirilmesinin gerekliliğini vurgulamaktadır.

Lately in Europe and more recently in Turkey, the emergence of natural gas as the premier fossil fuel for co-generation of electricity and fast growing residential/commercial gas markets underscored the need for underground storage for reasons of safety, security, and environmental quality. Natural gas consumption and operations in Turkey have been significantly increased in recent years. Based on October 1996 figures there are 512000 residential gas consumers in Istanbul, 172000 in Ankara, 71000 in Bursa, and 10000 in Eskişehir. A total of 1.6 million residential units in Istanbul, Ankara, Bursa, İzmit, Adapazarı, and Eskişehir are planned to be potential gas users. Particularly air pollution problems in big cities have forced the regional authorities to further extend the existing gas distribution projects. All types of natural gas sales, whether domestic, commercial, industrial, or space - heating, present variable factors. Probably the most difficult load for the distributor to meet is the space - heating load. It varies from a minimum of zero in the summertime to a maximum that can occur any time during the cold winter months. Studies indicate that the 70 per cent of yearly residential gas demand for space heating in Istanbul and Ankara is consumed during the coldest 4 months between December and March. Demand for gas during summer months is almost negligible. Since the amount of gas supplied by the major pipeline transporting Russian natural gas is constant throughout the year, the higher gas demand by the residential consumers in big cities during the colder period of the year cause operational problems. So that, predictions of residential consumption must be made a year or more in advance to ensure adequate supplies of gas and facilities to handle the predicted distribution. This study aimed to investigate two important aspects of the fast developing natural gas industry in Turkey: (1) the gas consumption potential of the space-heating sector, and (2) modeling a recently discovered gas field (the Northern Marmara gas field) as an underground gas storage reservoir. First part of the study is conducted to determine the maximum possible demand if gas is consumed by the residential areas on or nearby the gas distribution pipelines existing, under construction and planned. The results of such a study yield the approximate magnitude of the possible gas shortages in future and also provides some insights for the related state and local municipal energy technical authorities. Second part of this thesis presents a preliminary feasibility study of the Northern Marmara gas field as an underground storage reservoir. Knowing the fact that the development of the underground gas storage facilities is a must in Turkey, the salt domes near Salt Lake (Tuz Gölü) and Northern Marmara gas field seem to be the only possible candidates at present for the underground gas storage purposes. From the technical and economical point of view Northern Marmara gas field provides more advantages (already discovered, partly developed, has higher gas in place) than the possible storage projects in salt domes. Therefore the Northern Marmara gas field was chosen to be modeled as an underground gas storage reservoir. In order to predict the potential gas consumption, the average gas consumption of a residence and the number of residences using natural gas for space-heating must be known or estimated. For this purpose, population of the cities located nearby the existing, under construction and planned pipelines in Turkey were determined using the data of State Statistics Institute. Then the number of residences were estimated from the population data. The degree-day method were utilized to determine potential residential consumption. Considering natural gas consumption of 100 %, 50 %, and 25 % of residences, gas consumption potential for space-heating was predicted for the years 1996, 2000,2005, and 2010. Results are presented in Table 1. As given in Table 1, residential consumption in 2010 is nearly 16.4x10^ sm^ if all of the residential units (100 %) in cities on or nearby gas pipelines use natural gas for space-heating. However, according to the figures given by the Ministry of Energy and Natural Resources the total natural gas supply and the gas supply for space-heating sector are projected to be between 30-50 xlO^ sm-* and 4.5-7.5 xlO^ snv* in 2010, respectively. The maximum amount of gas supply projected for the residential heating sector in 2010 (7.5 xlO^ snv*) would provide energy for only about 46 % of residences. It is easily seen that unless the amount of gas supply is increased, the number of residential units consuming gas for space-heating purposes is limited. In regions which experience large seasonal variations in temperature, residential gas consumption is increased during the coldest months, and gas demand can not be provided by major natural gas pipeline. The most common way to balance between higher winter gas demand and constant gas supply is to use the underground storage facilities. Underground storage is an efficient and an economical method to handle the load-factor problem in distribution of space-heating gas. Storage reservoirs are the warehouse to give a ready supply of gas that can serve a market with high peak demands in cold weather. The natural gas simply is injected into underground storage reservoirs when market demand falls below the supply available from the pipeline. It is withdrawn from the storage to supplement the steady supply from the pipeline when the demand exceeds the supply. There are three types of underground storage: - in porous media, aquifers or depleted gas/oil fields - in salt caverns, - in rock caverns or abandoned mines. IX o es "O O o es o" o o c^ VO F- I.s c o I 3 e o U S.S3 "S a en Depleted gas/oil fields are prime candidates for conversion to storage. Gas is injected into the porous media during the low load periods (summer) and is withdrawn during high load periods (winter). An underground storage in aquifers is made by removing out part of the water from the aquifer reservoir by means of gas injection. Underground storage in salt caverns is also made by water leaching in salt formations. The stored gas is considered in two parts: - base gas or cushion gas, - top gas or working gas. The working gas is that portion of the storage gas which is sent to distribution in response to market demand. It is replenished at the end of each withdrawal cycle by injection into the storage field. The difference between the total gas in storage and the working gas is called base gas. The main role of the base gas is to provide the pressure energy necessary for delivering the storage gas to the pipeline at a required rate. The possibilities of underground gas storage in Turkey are discussed in the second part of this study. In spite of fast increasing natural gas consumption there has not been any considerable underground gas storage developments in Turkey. Prediction of gas consumption indicates possible gas shortages if underground gas storage facilities are not developed soon. Projects should have priorities in energy planning. Beside to meet winter gas demand, underground gas storage is necessary to be independent from only one source of supply and to make a strategic reserve in Turkey. The Liquefied Natural Gas (LNG) terminal in Marmara Ereğlisi can be used as a storage to meet winter gas demand. However, this LNG facility is planned to supply gas to a nearby power plant rather than being used as a storage facility. The Northern Marmara gas field, a recently discovered and developed field in the Thrace region, was investigated as an underground gas storage reservoir candidate. Among the several gas fields in Thrace region, the Northern Marmara gas field was chosen for investigation because the permeability and areal extent of this gas field are sufficiently large for gas storage purposes. The gas storage reservoir performance of the Northern Marmara gas field was studied using two approaches. The primary aim of the first modeling approach is to minimize number of wells for known base and working gas capacities, the production/injection rate and periods. Using material balance concept and deliverability equation, required number of wells are determined for certain base and working gas volumes and operation periods. Results are presented in Table 2. As given in Table 2, new wells are necessary in XI Table Base and Working Gas Capacities and Required Number of Wells as a Function of Production/Injection Periods. xn addition to existing three wells in the Northern Marmara gas field if the field is considered to be underground gas storage reservoir. For example, under conditions of 1.354x10^ sm3 working capacity, 100 day production/injection period and 70 bar minimum wellhead flowing pressure, nearly 33 wells are needed. This means that 30 wells are required to be drilled and completed if the field is to be operated as a storage reservoir under given conditions. The task in second modeling approach is to maximize working gas volume and peak rates for a particular configuration of reservoir, well and surface facilities, number of wells and production/injection periods. In this model, production performance curve is produced at constant minimum wellhead pressure, and injection performance curve is produced at the desired maximum bottomhole injection pressure. The intersection of the two curves gives base gas and maximum gas capacities subject to the given constraints. The difference between these two numbers gives the maximum working gas volume. Based on the results of this second modeling approach the base gas, maximum gas, and maximum working gas capacities for the Northern Marmara gas field were determined to be 2.05x10^ sm3, 3.35xl09 sm3, and 1.3x10^ sm3, respectively. The constant production/injection rates were calculated to be 0.216xl09 sm3 (7.65 MMSCFD) obtained by dividing the working gas by the number of production/injection days (120 days). The number of I/W (Input/Withdrawal) wells was assumed to be 50. The following results were obtained from this modeling study: 1. Modeling a gas reservoir for underground gas storage purposes requires an optimization approach correlating and combining the effects of important fluid, rock, field, well, and other operation parameters. 2.1n order to operate the Northern Marmara gas field as a storage reservoir with some respectable working gas volume (£lxl09 sm3), the number of wells required to maintain the field working at capacity varies between 20 and 50 depending on desired wellhead flowing pressure.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 1997
Keywords: Depolama sistemleri; Doğal gaz; Marmara bölgesi; Storage sistems; Natural gas; Marmara region